(untitled) (Kairaranga, 2020)
This professional inquiry investigates how Community of Learning Ka hui Ako across-community teachers (ACT) can support teacher confidence and perceived competence in relation to their culturally-responsive pedagogy. Communities of Learning Ka hui Ako are explored in terms of defining what makes a community successful and how they can be used as a vehicle for accelerating the achievement of Maori learners. A review of the literature surrounding culturally-responsive pedagogy, its enablers and barriers, as well as evidence that Communities of Learning Ka hui Ako can address this, is examined. A semi-structured interview was used to explore Community of Learning Ka hui Ako ACT perceptions of culturally- responsive pedagogy and successful practice. Findings from this inquiry suggest that the mechanism of Communities of Learning Ka hui Ako though the ACT is having a positive impact on teacher confidence and perceived competence in relation to culturally-responsive pedagogy through the explicit use of Kaupapa Maori principles to support and drive change.